More than a Slogan: Or, how we built a Social Justice Program that made our campus more Just - Hengen Fox, Nicholas (Radical Teacher, 2020)
Today on college campuses in the U.S., “social justice” is everywhere—a bright signal of some institutional wokeness in institutions that have not always been good or awake to the needs of many in their communities. In 2014, I joined the trend, as part of a small group of faculty and staff at Portland Community College, that created a concentration of courses called the Social Justice Focus Award and, the next year, built a curriculum for a capstone class called “Social Justice: Theory & Practice” (SJ210). This article shares this experience for faculty considering building such a course, program, or major; maybe you can learn from our successes (and our mistakes). But in telling this story, I am also tracing the contradictions tied up in the proliferation of “social justice” on college campuses. Even as a marking strategy, for higher ed to claim it’s doing social justice sparks off massive institutional identity conflicts. Higher education’s long-term investment in (scientific) objectivity, neutrality, of teaching students ‘how to think not what to think’ stands in direct contrast to doing the work of justice. So claiming to teach social justice—to grant degrees in it!—begs important questions about the kinds of promises we’re making to our students and our communities, to say nothing of our conception of who we are as institutions. I’ll argue here that if we teach social justice in the framework dictated by traditional higher ed commitments, we probably do a bad job. But we can make good on the promise of social justice if our courses and programs are (1) centered on a student-led, class-defined, campus-based project that (2) involves collective action. That work must be grounded in a classroom that is (3) explicitly not neutral. In our program, we don’t aim at global justice; we aim at making the changes we can make on campus. And what we’ve learned is that by starting there, our students are actually making the world more just. As our students learn to identify injustice, talk about it with others, and enact strategies for change, they are meeting the course’s learning outcomes while improving life for many on campus, including undocumented students, nonbinary students, and students living without housing. Their work has made “social justice” more than a slogan on our campus.